Occurrence of class B carbapenemase (Metallo-B-Lactamase)-producing healthcare-associated Pseudomonas aeruginosa isolates from The Philippine General Hospital (PGH) and characterization of the MBL genes - Esperanza, Joy B. Montecastro (Animo Repository, 2012)
Pseudomonas aeruginosa is the most commonly implicated opportunistic pathogen in nosocomial or healthcare-associated infections. Nosocomial infections due to P.aeruginosa are difficult to treat due to its multiple antimicrobial resistances that may be acquired or inherent to the organism. Among the resistance mechanisms, the production of class B carbapenemases or metallo--lactamases (MLs) has the most serious consequences as these hydrolyze most -lactams, including the last drug of clinical antimicrobials, i.e., carbapenems. In the present study, 230 P. aeruginosa isolates were obtained from patients with nosocomial infections who were confined at the Philippine General Hospital, Manila from August 15, 2010 to November 15, 2010. These isolates were tested for their antimicrobial susceptibility patterns or antibiograms using the disk diffusion method of Kirby and Bauer, and further studied for the occurrence of resistance due to ML production. The most potent antimicrobial drugs tested against the isolates were found to be aztreonam, amikacin and ceftazidime, with 10.87% of the isolates being completely resistant to aztreonam, 12.17% to amikacin and 13.04% to ceftazidime. ML production was shown by 37/ 43 (86.04 %) carbapenem resistant P. aeruginosa isolates using the imipenem/meropenem-EDTA disk screen test. Using IMP-F and IMP-R primers (blaIMP and 59-be) and VIM-F and VIM-R primers (attI and blaVIM ), which are specific for the two most commonly detected ML, PCR assay was performed on the isolates phenotypically positive for ML production. Twenty-one (21) isolates produced amplicons. Nucleotide sequencing and BLAST analysis confirmed 15 isolates with blaVIM-2 genes and one isolate with the blaIMP-26 gene. This is the first report on the occurrence of class B carbapenemase-producing healthcare-associated P. aeruginosa in the Philippines.